PENGARUH CITRA PERUSAHAAN DAN FASILITAS PERUMAHAN TERHADAP KEPUASAN KONSUMEN DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING (SURVEI PADA KONSUMEN PERUMAHAN PENI REGENCY SOLOBARU) - 88, suryani; 88, suryani (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2021)
THE EFFECT OF COMPANY IMAGE AND RESIDENTIAL FACILITIES ON CUSTOMER SATISFACTION WITH CONSUMER TRUST AS AN INTERVENING VARIABLES (Survey on Residential Consumers of Peni Regency Solobaru). Postgraduate Program in Management Masters Program, Slamet Riyadi University, Surakarta. January 2021. This study aims to: (1) analyze the significance of the influence of corporate image on consumer confidence in Peni Regency Solobaru residential. (2). to analyze the significance of the effect of residential facilities have a significant effect on consumer confidence in residential Peni Regency Solobaru. (3). to analyze the significance of the influence of corporate image on consumer satisfaction in Peni Regency Solobaru residential. (4). to analyze the significance of the effect of residential facilities on consumer satisfaction in residential Peni Regency Solobaru. (5). to analyze the significance of the influence of consumer trust on consumer satisfaction in Peni Regency Solobaru residential. (6). to analyze the role of trust in mediating the influence of company image on consumer satisfaction in residential Peni Regency Solobaru and (7). to analyze the role of trust in mediating the effect of company facilities on consumer satisfaction at residential Peni Regency Solobaru. The population of this research is 50 people of Peni Regency Solobaru residential. The research sample was taken as a whole from the total population. The data collection technique used a questionnaire that had been tested for validity and reliability. The results of data collection obtained a questionnaire that was entered by 50 respondents. The data analysis technique used is the path analysis test with multiple linear regression through the classical assumption test. Where all the assumptions as the prerequisite for regression can be fulfilled, namely the absence of multicollinear cases and residual variances in normal distribution. The results of the analysis are as follows: (1) company image has a significant effect on consumer confidence in residential Peni Regency Solobaru, (2). Residential facilities have no significant effect on consumer confidence in residential Peni Regency Solobaru, (3). Company image has a significant effect on consumer satisfaction at residential Peni Regency Solobaru, (4). Residential facilities have a significant effect on consumer satisfaction of residential Peni Regency Solobaru, (5). Consumer confidence has a significant effect on consumer satisfaction in Peni Regency Solobaru residential, (6). trust mediates a significant effect of corporate image on consumer satisfaction in residential Peni Regency Solobaru, (7). trust does not mediate the effect of residential facilities on consumer satisfaction residential Peni Regency Solobaru. Based on the results of this study, some suggestions as a follow-up to this study are policy to improve the company's image and residential facilities in order to increase customer satisfaction, so that consumers can trust Peni Regency company so that it can increase home sales. Keywords: image, facilities, trust, customer satisfaction.